EXPLORING TEACHERS’ CONCEPTIONS OF SPIRITUALITY AND THEIR PERCEPTIONS ABOUT ITS INTEGRATION INTO EFL CLASSROOMS IN PESANTREN-BASED MADRASAS - Kasyfur Rahman (Universitas Islam Negeri Mataram, 2023)
This study aims to describe madrasa English teachers? conceptions of spirituality and their perceptions on its integration into classroom at one of Islamic boarding schools in Lombok, West Nusa Tenggara. This study involved four teachers from each of the four educational units, Junior high school (male and female) and Senior high school (male and female). Data were obtained through semi-structured interviews with the four teachers and through the analysis of teaching documents. The findings orchestrate that spirituality, as conceptualized by these teachers, is centered upon divinity thus establishing a transcendental bond in which God?s role is related to all matters including their personal being and becoming as well as their connectedness with other humans and nature. This is seemingly in contrary with contemporary western account that narrows down the role of religiousity on spirituality. Additionally, through thematic analysis, four major themes related to their perceptions of integrating sprituality into classroom were obtained, namely the important role of spirituality in English language teaching, the potential for integration into learning, challenges in integrating and the integration models. All teachers considered that Islamic spirituality plays a central role, especially in learning and teaching activities, and can be integrated through classroom instructional activities and teaching materials such as greeting and praying, using Islamic nuanced media, and teaching texts with the theme of Islamic figures. This is supported by the core competence elements contained in the learning syllabus about the practice of religious teachings. However, the teachers also revealed the various challenges in carrying out the integration in question, including students' comprehension, difficulty in exemplifying the connection between spiritual values and existing teaching materials, and teacher qualifications.